ANALISIS ECONOMIC VALUE ADDED (EVA) DALAM HUBUNGANNYA DENGAN HARGA SAHAM PADA PERUSAHAAN JASA TRANSPORTASI YANG LISTING DI BURSA EFEK JAKARTA PERIODE 2003—2005 - RIZAL, SEFCHO; RATNA SARI, M.M. (Jurnal Ilmiah Akuntansi dan Bisnis, 2008)
Capital is an important component that determines company’s operation. Issuing stock would be effective if it can add value to the company economically. One approach that can be implemented for company valuation is Economic Value Added (EVA), which takes into account the cost of capital. This cost is formerly abandoned by companies, although it is very crucial in value creation for the company. This research tries to asses company’s financial performance using EVA approach and correlate it to stock price. Research objects cover transportation service companies listed on the Jakarta Stock Exchange (JSX) during period of 2003-2005. The companies have important roles in mobilizing product and services needed by society. The result shows that most transportation companies listed on the JSX during 2003- 2005 have not able to create economic value added. Result of correlation analysis shows that the relationship between EVA value and stock price is not in the same direction (negative), very weak, and not significant.
Keywords: economic value added analysis, stock price.